The TRPA1 channel in migraine mechanism and treatment. (May 2014) - Benemei, S; Fusi, C; Trevisan, Gabriela; Geppetti, Pierangelo
<x xml:space="preserve">Abstract</x> Migraine remains an elusive and poorly understood disease. The uncertainty is reflected by the currently unsatisfactory acute and prophylactic treatments for this disease. Genetic and pharmacological information points to the involvement of some transient receptor potential (TRP) channels in pain mechanisms. In particular, the TRP vanilloid 1 (TRPV1) and TRP ankyrin 1 (TRPA1) channels seem to play a major role in different models of pain diseases. Recent findings have underscored the possibility that TRP channels expressed in the nerve terminals of peptidergic nociceptors contribute to the migraine mechanism. Among this channel subset, TRPA1, a sensor of oxidative, nitrative and electrophilic stress, is activated by an unprecedented series of irritant and pain‐provoking exogenous and endogenous agents, which release the pro‐migraine peptide, calcitonin gene‐related peptide, through this neuronal pathway. Some of the recently identified TRPA1 activators have long been known as migraine triggers. Furthermore, specific analgesic and antimigraine medicines have been shown to inhibit or desensitize TRPA1 channels. Thus, TRPA1 is emerging as a major contributing pathway in migraine and as a novel target for the development of drugs for pain and migraine treatment. Linked Articles This article is part of a themed section on the pharmacology of TRP channels. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2014.171.issue‐10